Sexual dimorphism in unfused hyoid bones using weight as a parameter - Tyagi, Ashish; Chawla , Hitesh (Journal of Indian Academy of Forensic Medicine, 2019)
The present study aims to determine the sexual dimorphism of unfused hyoid bone by using weight as a parameter. 286 unfused hyoid  bones of known sex obtained from the cadavers brought to the mortuary for autopsy were included in the study. 4 measurements were  made: weight of the right cornua, weight of the left cornua, weight of the body of the hyoid, and weight of the entire hyoid bone.  Measurements were done using an electronic weighing scale and the observations were tabulated. All the measurements in male hyoid  bones were greater than the measurementsin female hyoid bones. Univariate discriminant analysis was conducted on the data to  estimate sex from the weight of the unfused hyoid bone. The accuracy ranged from 67.5% to 76.6% [62.1% - 73.4% in males and  75.2% - 81.2% in females]. Weights of different parts of unfused hyoid bone showed statistically significant results and can be used to  estimate sex along with other parameters.
Keywords: Unfused hyoid bone; Weight; Sex determination; Sexual dimorphism; discriminant function analysis